CO2 capture in cement plants by "Tail-End" Calcium Looping process. (August 2018) - Lena, E. De; Spinelli, M.; Romano, M.C.
Abstract: In this work the integration of the Calcium-Looping (CaL) process, used as a post-combustion CO2 capture system, into a cement kiln was analyzed by means of process simulations. The results show that capture efficiencies of about 90% can be achieved with operating conditions of CaL reactors similar to those for power generation applications. The integration of the CaL process increases the fuel consumption of the cement kiln, but the additional primary energy introduced for sustaining this CO2 capture process can be efficiently exploited for raising HP steam and producing electricity in a Rankine cycle.